2018
DOI: 10.6061/clinics/2018/e565s
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic testing in oncology: a Brazilian perspective

Abstract: Pharmacogenetics, a major component of individualized or precision medicine, relies on human genetic diversity. The remarkable developments in sequencing technologies have revealed that the number of genetic variants modulating drug action is much higher than previously thought and that a true personalized prediction of drug response requires attention to rare mutations (minor allele frequency, MAF<1%) in addition to polymorphisms (MAF>1%) in pharmacogenes. This has major implications for the conceptual develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…This is in line with the EMA statement that PGx information are preferentially present in drug labels having antineoplastic properties [10]. In the field of oncology, pharmacogenetic biomarkers represent a complex combination of germline and somatic variants [11]. Importantly, somatic mutations in tumor cell are increasingly implicated biomarkers in targeted therapy, applied in treatment selection, and are also often associated with treatment efficacy [12].…”
Section: Discussionsupporting
confidence: 55%
“…This is in line with the EMA statement that PGx information are preferentially present in drug labels having antineoplastic properties [10]. In the field of oncology, pharmacogenetic biomarkers represent a complex combination of germline and somatic variants [11]. Importantly, somatic mutations in tumor cell are increasingly implicated biomarkers in targeted therapy, applied in treatment selection, and are also often associated with treatment efficacy [12].…”
Section: Discussionsupporting
confidence: 55%
“…There are ethnic differences in polymorphisms of genes involved in the metabolism of paclitaxel, especially in CYP2C8 and CYP3A4/5 enzymes [ 23 ]. There are few data about distribution of pharmacogenetics polymorphisms among Brazilians, besides the fact that the Brazilian population is highly heterogeneous and admixed, which may cause high heterogeneity of drug responses [ 29 ]. A small study showed that the frequency of CYP2C8*2, for example, is similar to other registries, being more common in Brazilian black population (13% of the sample) and rare for white and Asian Brazilians (1 and 0%, respectively) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of Native populations living in reservations areas in Brazil disclosed the highest range of rs116855232 MAF (19.4–31.7% in Kaingang and Guarani) reported so far for any population worldwide [8]; In other Native American populations from Brazil, the MAF of rs116955232 was reported as ranging from 5.2% in Xavante (Center-West region; [8]) to 9.4% in Amazonian groups [9]. For comparison, in admixed cohorts from the Southeast region of Brazil, with average Native ancestry <10% [7], the MAF of rs116855232 is < 1.3% [6,10].…”
mentioning
confidence: 99%